PERFORMANCE OF MACHINE PLANTED CHICKPEA (Cicer arietinum L.) AS INFLUENCED BY DIFFERENT SEED RATES AND NUTRIENT MANAGEMENT PRACTICES IN SOUTHERN TELANGANA ZONE - S. TRIVENI and M. YAKADRI, M. KARTHIKA, K. BHANU REKHA, KASBE SUDHANSHU SUDHAKAR, A. MADHAVI, P. RAJAIAH (The Journal of Research, PJTSAU, 2023)
A field experiment was conducted in vertisols of Agricultural Research Institute, Main farm, Professor Jayashankar Telangana State Agricultural University, Hyderabad during rabi 2020-21 and 2021-22 to study response of chickpea (JG-11) to different seed rate with CIAE planter and nutrient management. The experimental plots were laid out in split plot design with different seed rates (4) as main plots and nutrient management as sub-plots (7). Application of 105 kg ha-1 resulted in highest dry matter production (5296 and 5742 kg ha-1), seed yield (2548 and 2615 kg ha-1) and haulm yield (2764 and 3054 kg ha-1) among the seed rate treatments during 2020-21 and 2021-22 respectively. Among the nutrient management practices, application of 125 % RDF along with soil application of microbial consortia (N – Azotobacter + PSB + KRB+ ZnSB) @ 5 kg ha-1 recorded highest dry matter (5359 and 5606 kg ha-1), seed (2522 and 2640 kg ha-1) and haulm yield (2663 and 2936 kg ha-1) during 2020-21 and 2021- 22 respectively.